2007
DOI: 10.1016/j.ccr.2007.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Recognition of SMRT/N-CoR by the MYND Domain and Its Contribution to AML1/ETO's Activity

Abstract: AML1/ETO results from the t(8;21) associated with 12%-15% of acute myeloid leukemia. The AML1/ETO MYND domain mediates interactions with the corepressors SMRT and N-CoR and contributes to AML1/ETO's ability to repress proliferation and differentiation of primary bone marrow cells as well as to enhance their self renewal in vitro. We solved the solution structure of the MYND domain and show it to be structurally homologous to the PHD and RING finger families of proteins. We also determined the solution structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
143
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(149 citation statements)
references
References 56 publications
6
143
0
Order By: Relevance
“…ZNF651 and ZNF652 carboxy-terminal proline-rich region conforms to this motif. MYND domains are defined by a C 4 -C 2 HC consensus and are frequently implicated in transcriptional repression [10,11]. Interaction of ZNF651 and ZNF652 with CBFA2T3 through their carboxy-terminal prolinerich conserved sequence further emphasises the functional significance of proline-rich regions in protein-protein interaction and cell signaling [12].…”
Section: Discussionmentioning
confidence: 99%
“…ZNF651 and ZNF652 carboxy-terminal proline-rich region conforms to this motif. MYND domains are defined by a C 4 -C 2 HC consensus and are frequently implicated in transcriptional repression [10,11]. Interaction of ZNF651 and ZNF652 with CBFA2T3 through their carboxy-terminal prolinerich conserved sequence further emphasises the functional significance of proline-rich regions in protein-protein interaction and cell signaling [12].…”
Section: Discussionmentioning
confidence: 99%
“…For the stereospecific assignments of methyl groups of leucines and valines, 10% fractional 13 C-labeled eTAFH-HEB was prepared by growing cells in minimal media containing 90% 12 C-glucose and 10% 13 C-glucose. U-[ 15 N, 13 …”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…For the stereospecific assignments of methyl groups of leucines and valines, 10% fractional 13 C-labeled eTAFH-HEB was prepared by growing cells in minimal media containing 90% 12 C-glucose and 10% 13 C-glucose. U-[ 15 N, 13 where ␦ i is the chemical shift at each titration point, L ti is the total ligand concentration at each titration point, P t is the total protein concentration, and ␦ b is the chemical shift of the fully bound form. 24,25 K d and ␦ b were determined by an iterative fitting routine.…”
mentioning
confidence: 99%
“…51 We therefore tested whether the NHR2 domain-deletion mutant of AML1-ETO influences its DNA-binding affinity. The DNA-binding affinity assay with human separase TC probe revealed that wild-type AML1-ETO has a much higher binding affinity than the NHR2-deleted AML1-ETO ( Figure 3F lanes 3 and 4).…”
Section: Higher Dna-binding Affinity Of Aml1-eto For Double Aml1 Sitementioning
confidence: 99%